ANALISIS PENGEMBANGAN ELECTRONIC GOVERNMENT DI KABUPATEN DEMAK (STUDI KASUS WEBSITE PEMERINTAH KABUPATEN DEMAK) - Jatmiko, Andityo Aryo; Astuti, Retno Sunu (Journal of Public Policy and Management Review, 2018)
This research aims to find out and analyze the development of electronic government in Demak regency especially about Demak Regency Government website’s and influencing factor in development of electronic government. Dinas Komunikasi dan Informatika Demak District as an instituion that manages the website and responsible in online-based public service in Demak District that still has obstacles. This research is a descriptive qualitative research with data collection through interview and document study. Informants was taken from the Head of Informatics Deparment of Dinas Komunikasi dan Informatika Demak, employees of Dinas Komunikasi dan Informatika and Citizens. In this study, Researcher used the stages of electronic government development and succesfull elements of electronic government development. The result show that the development of electronic government has not provided complete website content. Not ready yet in some Institution to website management. Lack of human resources which capable to operating or managing a website. Limited funding in order to fulfill the needs of electronic government development. Based on the result of this study, it can be concluded that in general the development of electronic government in Demak District is quiet good, although there still some elements must be improved. The research suggest to increase the amount of competent human resources in informatics technology field next year.